Evaluating the efficacy of pars plana vitrectomy in the management of endophthalmitis after following the endophthalmitis vitrectomy study: A systematic review and meta-analysis - Maria Angelia; Yufilia Suci Amelia; Ivana Beatrice Alberta; Stefany Tanto; Kevin Gracia Pratama (Tzu Chi Medical Journal)
Endophthalmitis is a devastating eye complication that requires prompt and effective treatment. A pivotal study in the field of endophthalmitis treatment is the endophthalmitis vitrectomy study (EVS), conducted over a decade ago. The primary objective of this study was to assess the effectiveness of pars plana vitrectomy (PPV) as a treatment option for endophthalmitis following the EVS study. We conducted a comprehensive search across three databases: PubMed, EBSCO host, and ProQuest. Reference lists of published articles were searched. Our study encompassed research conducted between January 2013 and January 2023 to ensure the most up-to-date findings. The best-corrected visual acuity (BCVA) in logMar, causative agents, and predicting factors for visual outcome were evaluated. Nine studies involving 351 eyes were included in the study; however, only eight were included in the meta-analysis. We observed a significant BCVA improvement compared to baseline at 1 month, >1–3 months, >3–6 months, and ≥12-month follow-up, with mean differences of 1.06 (P < 0.001), 1.25 (P < 0.001), 1.41 (P < 0.001), and 1.01 (P < 0.001), respectively. A causative organism was cultured in 61.4% of cases, and the majority of them were Coagulase-negative Streptococcus, Staphylococcus aureus, and Streptococcus sp. Factor associated with better visual acuity includes a younger age, lower intraocular pressure, and culture-negative endophthalmitis. Meanwhile, culture-positive endophthalmitis particularly Streptococcus sp., lower baseline vision, and presence of retinal detachment at initial presentation were identified as a prognostic for poorer visual outcome. PPV demonstrated a significant visual gain in patients with endophthalmitis in the 1st, 3rd, and 6th months. However, caution is warranted in drawing a definitive conclusion.